Over-expressed Phospholamban in Cancer-associated Fibroblasts Is a Driver for CMS4 Subtype Colorectal Cancer FormationSummary - Tao Li; Yuxiang Fei; Xu Sun; Jun Zhu; Xin Fang; Fanjun Meng; Danyi Wang; Xu Zhang; Chao Liu; Qianming Du (Cellular and Molecular Gastroenterology and Hepatology)
Background & Aims: Heterogeneity is the malignancy feature of colorectal cancer (CRC), which augments the difficulty of CRC treatment. Consensus molecular subtypes (CMSs) classified CRC into 4 subtypes. CMS4 is the most aggressive subtype, characterized with epithelial mesenchymal transition (EMT) and angiogenesis activation. However, the mechanism of CMS4 formation still remains unclear. We aimed to investigate the role of phospholamban (PLN) on CMS4 formation. Methods: Immunohistochemistry and Western blotting were used to detected PLN expressions. Transwell and wound-healing assays were used to evaluate migration and invasion of HCT116 and HT29. Tube formation assay was used to evaluate angiogenesis of HUVECs. GST pull-down was used to detected the interaction between PLN and AXIN2. The CAF-CT26 spleen co-transplantation mouse model was built to evaluate PLN’s effects on CRC metastasis. Results: PLN knockdown reversed CAFs’ conditional medium (CM)-induced EMT, cell migration, and angiogenesis (P < .01). PLN strongly bound to AXIN2, the main component of β-catenin degradation complex, and PLN knockdown increased β-catenin ubiquitination in CAFs (P < .01). PLN knockdown blocked GREM1 secretion (P < .01), and PLN overexpression-induced EMT, cell migration, and angiogenesis were blocked by anti-GREM1 neutralizing antibody (P < .01). Knockdown of BMP2 and VEGFR2 reversed CAFs’ CM induced EMT and angiogenesis effects, respectively (P < .01). PLN knockdown attenuated CAFs mediated tumor promoting effects in vivo (P < .01). Conclusions: PLN competitively binds with AXIN2 to increase β-catenin activity in CAFs. β-catenin signal induces GREM1 secretion, driving EMT and angiogenesis via BMP2 and VEGFR2, respectively. These findings demonstrate that PLN is a driver for CMS4 formation.